Phosphate availability, P-uptake, phosphatase, and yield of maize (Zea mays L.) affected by kaolin based P-solubilizer and P fertilizer in Inceptisols - Fitriatin, Betty Natalie; Budiman, Muhammad Nafariz; Suryatmana, Pujawati; Kamaluddin, Nadia Nuraniya; Ruswandi, Dedi (Universitas Padjadjaran, 2023)
Inceptisols have problem in phosphate availability. Soil P content is very low available to plants because it is bound by soil colloids. One of the efforts to increase the P nutrient in the soil in a sustainable way by using P-Solubilizers that can dissolve phosphate in the soil so that it is available for plants. The purpose of experiment was to determine the effect of the combination dose of kaolin based P-Solubilizer and P fertilizer for improving P availability, P uptake, phosphatase, and maize yield on Inceptisols. The kaolin-based P-Solubilizer was used a consortium of phosphate solubilizing microbes (PSM) consisting of Bacillus subtilis, Burkholderia cepacea, Pseudomonas mallei, and Trichoderma asperellum. This experiment was conducted in the experimental field of the Laboratory of Soil Chemistry and Plant Nutrition, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, from July to December 2021. The experiment used a randomized block design (RDB) method with nine treatments and three replications, with details of 0 P-Solubilizer + 0 P-fertilizer; 100% P-fertilizer; 100% P-solubilizer; and combination 50%, 75 %, 100%, and 150% P-solubilizer with 50%, 75%, and 100% P-fertilizer. P-solubilizer 100% recommended dose 50 kg ha-1 and P-fertilizer recommended dose 100 kg ha-1. The results showed that the dose of 100% P-Solubilizer (50 kg ha-1) + 75% P (75 kg ha-1) showed the best results in increased P-availability (346,93%), P-uptake (312,5%), Phosphate activity (33,5%), and maize yields (48,09%) compared to without application of P-solubilizer and P-fertilizer. This consortium isolate could be developed as a P-Solubilizer with the ability to increase the efficiency of P up to 25%.